Revisión crítica de la literatura sobre el análisis financiero de las empresas - Salvador Aníval Ochoa Ramírez; Juan Alfonso Toscano Moctezuma (Nóesis)
The analysis of financial statements by ratios has been, for decades, the traditional approach to diagnose the economic and financial situation of companies. The objective of the present article is to critically revise the most relevant bibliography, fundamentally, of empirical character related to the study of the financial analysis of accounting statements of companies using what's commonly known as "financial ratios".